The orange tree - Li, Dong 1984- (The University of Chicago Press, 2023)
"Comprised of a series of long, lyrical narrative poems, Dong Li's debut collection of poetry braids forgotten histories, family sorrows, and political upheavals into a panoramic view of China and the people who embody it across generations. The Orange Tree navigates the personal and the political, grounding its abstract meditations in the raw, worldly experience in characters whose lives bear striking affinities across disparate eras. Cycling between mythological time, ancient history, and modern memory, Li offers unexpected perspectives on epochs that resemble our own-not the least of which are the poems' unflinching meditations on the brutality of war. Throughout the book, images and phrases are compressed into portmanteaus of premonition, signaling as nouns the metaphoric inventions that one will come to find -- "the anguishednight," "the farawayorangetree," "the launderedyears," "the drifteddream." Like the legend of a map or the runes on a relic, these puzzles invite us to parse the words of The Orange Tree, breaking them apart and creating entrances that lead deeper into the elaborate architecture of Li's poetic world-building"--
Keywords: Poets, Chinese / 21st century; Poètes chinois / 21e siècle; POETRY / Subjects & Themes / Family; POETRY / Asian / Chinese; Poets, Chinese; 2000-2099; poetry; Poetry; Poésie